Efficacy of mosapride citrate with a split dose of polyethylene glycol plus ascorbic acid for bowel preparation in elderly patients: A randomized controlled trial - Lee, Jin (Medicine (Baltimore), 2020)
BACKGROUND/AIMS: Old age is a risk factor of suboptimal bowel preparation. This study aimed to evaluate the efficacy of mosapride citrate with a split dose of polyethylene glycol (PEG) plus ascorbic acid for bowel preparation in elderly patients (aged ≥65 years) before they underwent a colonoscopy. MATERIALS AND METHODS: This prospective investigator-blinded randomized study was conducted from November 2017 to October 2018. The patients were randomly divided into 2 groups, a mosapride group (mosapride citrate with a split-dose of PEG plus ascorbic acid) or a non-mosapride group (a split-dose of PEG plus ascorbic acid alone). Mosapride citrate 15 mg (Gastin CR) was administered once with each split-dose of the bowel preparation. The bowel preparation quality was assessed using the Boston Bowel Preparation Scale (BBPS). RESULTS: A total of 257 patients were finally included and analyzed in our study. The total BBPS score was significantly higher in the mosapride group than in the non-mosapride group (8.53 vs 8.24, P = .033). The BBPS scores of the right colon and mid-colon were 2.75 vs 2.61 (P = .044) and 2.89 vs 2.79 (P = .030), respectively. The rate of adequate bowel preparation (BBPS ≥ 6) was similar in both groups (98.4% vs 98.5%, P = .968), while the rate of excellent bowel preparation (BBPS = 9) was higher in the mosapride group than in the non-mosapride group (73.8% vs 61.1%, P = .029). The total incidence of adverse events during the administration of the bowel cleansing agent, particularly abdominal fullness, was lower in the mosapride group (11.9% vs 30.5%, P < .001). CONCLUSION: The administration of mosapride citrate with a split-dose of PEG plus ascorbic acid in elderly patients showed an increase in bowel preparation efficacy and reduced adverse events, particularly abdominal fullness, during the administration of a bowel cleansing agent.